Public Sector Policy of Estimating Model for Renewable Energy - Suhendro, Saring; Matalia, Mega; Sembiring, Sari Indah Oktanti (International Journal of Energy Economics and Policy, 2021)
Renewable energies are crucially needed right now. One of the them is ethanol as a non-fossil energy source. Data time-series of world demand for ethanol are very interesting to find its forecasting models, so that the production targets can be more accurate. Generalised auto-regressive conditional heteroscedasticity is one of the best models we use. Our findings AR(1) - Generalised Auto-Regressive Conditional Heteroskedasticity (GARCH) (1,1) modelsare considered as a good-fit measurement in predicting ethanol demand. Increasing the number of demand should be considered with the number of its processes. In this paper, we combine an analysis of economic considerations (predicting demand levels) with a political analysis of policies (describing renewable energy policy options). Keywords: Renewable energies, Ethanol, GARCH model, Forecasting, Energy policy JEL Classifications: C5, C53, H2, H25, Q4, Q47 DOI: https://doi.org/10.32479/ijeep.11323